The Kurdistan Region of Iraq : Reforming the Economy for Shared Prosperity and Protecting the Vulnerable - World Bank Group (World Bank, Washington, DC, 2016)
The Kurdistan Region of Iraq (KRI) is a constitutionally recognized semiautonomous region in northern Iraq. Its government, the Kurdistan Regional Government (KRG), based in Erbil, has the right, under the Iraqi constitution of 2005, to exercise legislative, executive, and judicial powers according to the constitution, except in what is listed therein as exclusive powers of the federal authorities. The Iraqi constitution defines the Kurdistan Region as a federal entity of Iraq. KRG has a parliamentary democracy with a regional assembly that consists of 111 seats. KRI has been largely immune to the insecurity and conflict witnessed elsewhere in Iraq, especially following the 2003 Iraq War. KRG is facing a wide range of immediate and medium to longer-term challenges that are intrinsically linked to the overall macroeconomic situation of Iraq as well as the regional and global environment. The immediate challenge consists in coping with (a) the deep fiscal crisis, and (b) the security and social problems brought about by the conflict with the Islamic State in Iraq and Syria (ISIS) group and the resulting influx of Syrian refugees and Iraqi Internally Displaced Persons (IDPs). These challenges are clearly immediate priorities for the KRG, and will bear significant repercussions nationally and internationally if inadequately addressed. The medium to longer-term challenges pertain to moderating dependence on the oil sector and transforming the KRI economy into a diversified one that supports private sector-led economic growth and job creation in a sustainable manner.